Salivary testosterone and cortisol levels in borderline personality disorder before and after a 12-week group dialectical behavior therapy intervention - Dyson, Tori; Thomas, Susan J.; Townsend, Michelle L.; Finch, Adam; South, Alexandra; Barkus, Emma; Walter, Emma; Mendonca, Carley; Grenyer, Brin F. S.; Pickard, Judy A. (Frontiers in Psychology, 2023)
Background: Borderline Personality Disorder (BPD) is a chronic, debilitating, and difficult to treat condition. BPD has recently been linked to steroid hormone dysregulation and medical conditions characterised by disturbed androgen metabolism. This study aimed to investigate cortisol and testosterone levels in BPD, and changes in hormones following psychological treatment. Methods: Participants with BPD (n = 33) completed a 12-week Dialectical Behavior Therapy group program. Pre and post salivary testosterone and cortisol were analysed. Baseline hormones in the BPD group were compared to age-andsex matched controls (n = 33). Non-parametric tests were utilised to investigate group differences, pre-post treatment hormone and symptom changes, and associations between symptoms and hormone levels. Results: Participants with BPD had significantly higher testosterone levels than controls. Mean testosterone levels in females with BPD were double that of female controls. Testosterone and cortisol levels were related, and some BPD symptoms were associated with with hormone levels. BPD symptoms reduced significantly with treatment, however pre to post hormone levels did not change.This study supports an association between BPD symptoms and neuroendocrine dysfunction at baseline, however we found no reduction in hormone dysfunction post treatment. Further research into relationships between stress signaling and neuroendocrine disturbances in BPD may inform aetiological and treatment models.